STRATEGI KOMUNIKASI PEMASARAN DALAM MEMPROMOSIKAN TRAINING CENTER(STUDI PADA PT INTI TAMA KARSA) - Ilona Vicenovie Oisina Situmeang (SEMIOTIKA: Jurnal Komunikasi, 2013)
PT. Inti Tama Karsa is one of the companies that engaged in services area that trying to improve the quality of the company by increasing the human resources competency through the training activities. Inti Tama Karsa Training Center (ITK-LC) is an education and training center. The aims of this research is to knowing what kind of marketing communications strategy that used by ITK-LC to promote their company. The method of research uses the qualitative approach with a descriptive style. The researchresults shows that the Marketing Communication that they performed is quite effective with some variety promotions that are used, such as advertising, sales promotion, personal selling, and publicity. The target market of this program is those people who come from working world and educational world. Based on the research results, ITK-LC’s Marketingshould create some new strategies, and not only focus on those five promotional mix tools.Keywords : Strategy, Marketing Communications, Promotion